Desenvolvimento territorial urbano: o caso da Região Metropolitana de Natal (RMN) no período (2011-2021) - Oliveira, Osmar Faustino de (2024)
The objective of this study was to analyze urban territorial development in the Metropolitan Region of Natal/RN in the period from 2011 to 2021, based on the elaboration of the Urban Territorial Development Index (IDTU) of the municipalities of the Metropolitan Region of Natal (RMN). The IDTU is composed of two dimensions: Quality of Life (QOL) and Urban Structure (EU). These dimensions are made up of variables: the Quality of Life (QOL) dimension was determined considering the variables Urban Formal Employment (EF); Urban GDP per capita (PU); Municipal Expenditure on Urban Planning and Housing (UH); Education Level of the Municipal Population (GI); Economically Active Population (EAP). The second dimension Urban Structure (EU) was created considering the variables Urban Public Transport (TC), Municipal Investment (IM); Expenditure on Municipal Health and Sanitation (SS); Municipal Budget Revenue (RO). The methodology used in this investigation consisted of bibliographical and quantitative research, as well as a data survey from various municipal, state and federal public administration bodies, such as the Ministry of Labor and Employment (MTE), Annual Information List Social Sciences (RAIS), Brazilian Institute of Geography and Statistics (IBGE), Institute of Applied Economic Research (IPEA/DATA), among others. In order to meet the objectives, an analysis was developed along four distinct axes: urban territorial development in the Metropolitan Region of Natal/RN was characterized; the dimensions and the Urban Territorial Development Index (IDTU) were estimated; the profile of urban territorial development in the municipalities of the Metropolitan Region of Natal/RN was analyzed and the occurrence or not of the expansion of the Urban Spot in the Metropolitan Region of Natal was identified. From these four axes it was also possible to develop a general analytical and information framework regarding the municipalities that make up the Natal Metropolitan Region (RMN). The research illustrated the degree of urban territorial development of the fifteen municipalities that make up the Natal Metropolitan Region (RMN). It was possible to identify the trajectory of each municipality in the period from 2011 to 2021. With the results of the IDTU estimate, municipalities with Dynamism were classified, that is, those that showed significant urban territorial development. Only five municipalities showed this dynamism, namely: Maxaranguape, São Gonçalo do Amarante, São José de Mipibu, Nísia Floresta and Ceará-mirim. A second classification adopted was the municipalities that presented Low Dynamism, that is, those that did not have an average performance in the IDTU. The municipalities of Monte Alegre, Parnamirim, Arês and Ielmo Marinho fell into this category. The municipality of Macaíba was found in the Stagnated category, that is, this municipality showed no change in the IDTU in the period from 2011 to 2021. In the RMN of the fifteen municipalities, five presented the classification of Depressed, that is, they are municipalities that throughout during the analysis period of this research did not show a reduction in their IDTUs, namely: Natal, Vera Cruz, Extremoz, Goianinha and Bom Jesus. Therefore, the present study illustrated that IDTU was significant in some municipalities, while others were depressed in relation to IDTU with low growth.